Cardioneuroablation of severe neurally mediated reflex syncope: the experience of two Portuguese centres. (19th May 2022) - Silva, G; Cardoso, F; Almeida, J; Fonseca, P; Ribeiro, S; Oliveira, M; Sanfins, V; Goncalves, H; Primo, J; Lourenco, A; Fontes-Carvalho, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Neurocardiogenic syncope (NCS) is the most frequent aetiology of syncope in young people. Cardioinhibition with asystole and/or transitory atrio-ventricular block induced by a massive vagal reflex is commonly observed in severe cases. According to the current guidelines, cardiac pacing is indicated in patients > 40 years old with severe, recurrent syncope and documented cardioinhibitory reflex. In younger patients there is no recommendation. Although pacing therapy could be effective, complications after pacemaker implantation are commonly seen. Recently, cardioneuroablation (CNA), a technique based on radiofrequency ablation of vagal ganglia, was developed to treat NCS as an alternative to pacemaker implantation in younger patients. However, this method is still evolving, and existing data refer to a small number of patients in a limited number of centres. Purpose: The aim of our study was to evaluate the efficacy and safety of CNA in patients with highly symptomatic neurocardiogenic syncope. Methods and Results: A total of 15 patients (11 male; aged 40.0 ± 13.3 years) who underwent CNA in two Portuguese centres between January 2019 and September 2021 were included. All had recurrent syncope with documented pauses at head-up tilt test, Holter or implantable loop recorder. Radiofrequency energy was applied in ganglionated plexi (GP) 1 (between the right upper pulmonary vein and the right atrium) in 14 patients, GP2 (between the superior vena cava and aortic root just above the right upper pulmonary vein) in 9 patients, GP3 (between the inferior vena cava and the right and left atrium) in 5 patients and GP4 (at the insertion of the left pulmonary veins) in 9 patients. The end point of procedure was the inhibition of the vagal response at target sites. Ablation was successfully performed in all patients. One patient had a convulsive episode after the procedure, requiring admission to intensive care but without neurological sequelae. No other major complications occurred. At a mean follow-up of 17.1 ± 12.6 months (range 3-35 months), 13 patients remained free of syncope. Other 2 patients had spontaneous recurrence of syncope (both 9 months after CNA) and underwent a new procedure. These 2 patients had a new symptomatic recurrence and a pacemaker was implanted. Conclusion: CNA appears to be an effective and safe treatment option for patients with refractory neurocardiogenic syncope and provide a new potential approach without pacemaker implantation.